TINJAUAN FIQH SIYASAH SYAR’IYYAH TERHADAP PERAN PEMIMPIN PEREMPUAN DALAM SISTEM KETATANEGARAAN DI KOTA MEDAN - Hudafi, Hamsah; Hayati, Amal; Diningrum, Sekar Ayu; Rangkuti, Vira Mumtaz Utami (Fakultas Syariah (Syari'ah Faculty ), 2023)
Women are often be the target of public outrage. The role of women in society is not only as a development process, but also as a strong structural foundation. Leaders are people who rule over an area. Managers must have a leadership spirit when moving around the environment. The results of the study show that the Medan City Human Resources Service is dedicated to providing services and work policies that are in line with the vision and mission of the city of Medan, especially for electronic services that offer electronic support. Free electronic services are available from Feel in the center of Medan City to make it easier for the general public to get services that are timely, efficient and in accordance with Siyasah syar'iyyah quotes. It has value both in the world and in Islam.